Clasificación de figurillas "coloniales" del centro de México: acercamiento temporal y función de la tradición escultórica. - Gómez-Llano, Sebastián; Basante Gutiérrez, Oscar (Memoria Americana)
The classification of materials is a key aspect of archaeological research. In central Mexico, the presence of clay figurines with European forms in non-Western archaeological contexts, referred to as colonial, has generated diverse interpretations about their use. This research presents a ceramic analysis that proposes a classification of the pieces and a chronological framework, in addition to explaining their use and function through the cross-referencing of historical sources with information obtained through ethnographic techniques. This allows us to point out that this type of figures are part of a new Mesoamerican religious manifestations and practices developed during the viceroyalty of New Spain, which have undergone processes of change and persistence until contemporary times.